Climate adaptation: Who pays and who benefits? - Peter Eckersley (EconPol Forum, 2025)
Investing in climate adaptation will be much more cost-effective than paying for emergency management and recovery after climate-related disasters. There is no simple "business case" for specific adaptation initiatives; governments need to take a very long-term perspective on capital spending. Some locations and population groups - often the least powerful members of society - are much more vulnerable to climate risks than others. Governments need to generate societal consensus on how to prioritize adaptation spending and protect vulnerable groups. Governments and private actors need to delineate their respective adaptation responsibilities.
Keywords: 330